Designing reinforced earth wall for seismic areas / Iqraz Nabi Khan, Swami Saran and Caroline Peter Diman - Nabi Khan, Iqraz; Saran, Swami; Peter Diman, Caroline (Universiti Teknologi MARA, Pulau Pinang & and Pusat Penerbitan Universiti (UPENA), 2005)
Reinforced earth wall has widely been adopted due to its economy, ease in construction and flexibility in nature. Keeping in view its nature being flexible, a pseudo static analysis has been carried out for the complete analysis and design of a reinforced earth wall having uniform surcharge on the wall and backfill. Both horizontal and vertical seismic forces have been taken into account to develop non-dimensional design charts. Use of these design charts has been illustrated by an example design.